Social Mobility in France 1720-1986: Effects of Wars, Revolution and Economic Change - Van Leeuwen, Marco H.D.; Maas, Ineke; Rébaudo, Danièle; Pélissier, Jean-Pierre (Journal of social history, 2016)
The most bask question concerning social mobility—whether it has decreased, increased or remained in a constant flux over time—was formulated a century ago by Sorokin. Despite the enormous progress made by historians and sodohgists, and the innumerable studies and the steady increase in the available data and methods of analysis, this question has still not been answered conclusively, because, we argue, of a lack of robust data covering a window of sufficient time span. In this article, we create and look through such a window, analysing intergenerational social mobility in France from the beginning of the eighteenth to the end of the twentieth century. We consider very long trends in total and rehtive mobility, and their association with the process of economic change, as well as perturbations of a shorter nature due to wars and revolutions. The results indicate that overall both absolute and rehtive mobility increased between 1720 and 1986, however not continuously, and not in synchronicity with the histoncal process of industrialization.